Zinc differentially modulates DNA damage induced by anthracyclines in normal and cancer cells - Wysokinski, D.; Blasiak, J.; Wozniak, K. (Experimental Oncology, 2012)
Zinc is one of the most essential trace elements in human organism. Low blood level of zinc is often noted in acute lymphocytic leukemia (ALL). Treatment with zinc adjuvant is hypothesized to accelerate recovery from ALL, and in conjunction with chemotherapy, cure ALL. Aim: We determined the effect of zinc on DNA damage induced by doxorubicin and idarubicin, two anthracyclines used in ALL treatment. Methods: The experiment was performed on acute lymphoblastic leukemia cell line (CCRF-CEM) and lymphocytes from peripheral blood of healthy, adult subjects. To evaluate the level of DNA damage the comet assay in the alkaline version was used. Results: We observed a significant difference in DNA damage level between normal and cancer cells in the presence of zinc. Cancer cells exhibited a significant increase of DNA damage in the presence of zinc, while in lymphocytes no such effect was observed. Conclusion: Our results suggest that zinc may protect normal cells against DNA-damaging action of anthracyclins and increase this action in cancer cells.